2018
DOI: 10.1098/rstb.2018.0160
|View full text |Cite
|
Sign up to set email alerts
|

5′ and 3′ modifications controlling RNA degradation: from safeguards to executioners

Abstract: RNA degradation is a key process in the regulation of gene expression. In all organisms, RNA degradation participates in controlling coding and non-coding RNA levels in response to developmental and environmental cues. RNA degradation is also crucial for the elimination of defective RNAs. Those defective RNAs are mostly produced by ‘mistakes’ made by the RNA processing machinery during the maturation of functional transcripts from their precursors. The constant control of RNA quality prevents potential deleter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 48 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…The stability and fate of mRNA molecules in the cell are under strict control, and at the end of their life cycle, RNAs undergo a carefully regulated degradation. The cap at the 5′-end and the poly(A) tail at the 3′-end are considered as major determinants of mRNA stability, but it can be also regulated by the other intrinsic features of transcripts, such as the sequence, length, and structure of UTRs and RNA modifications in UTRs [ 3 , 48 , 49 , 67 , 68 ]. Transcriptome-wide studies in vivo provide a growing number of evidence that RNA structural features can govern the RNA lifespan ( Table 2 ).…”
Section: Rna Structure In Relation To Rna Stability and Degradatiomentioning
confidence: 99%
“…The stability and fate of mRNA molecules in the cell are under strict control, and at the end of their life cycle, RNAs undergo a carefully regulated degradation. The cap at the 5′-end and the poly(A) tail at the 3′-end are considered as major determinants of mRNA stability, but it can be also regulated by the other intrinsic features of transcripts, such as the sequence, length, and structure of UTRs and RNA modifications in UTRs [ 3 , 48 , 49 , 67 , 68 ]. Transcriptome-wide studies in vivo provide a growing number of evidence that RNA structural features can govern the RNA lifespan ( Table 2 ).…”
Section: Rna Structure In Relation To Rna Stability and Degradatiomentioning
confidence: 99%
“…For example, we found that many miRNAs related to the RNA splicing pathway, where up-regulated in PDAC platelets, whereas the mature mRNAs associated to them where down-regulated. This may suggest that other regulatory mechanisms are involved in mature-RNA degradation such as 5′ and 3′ modifications on RNA extremities [ 61 ], RNA helicases, poly-A tail elongation, chaperones and silencing RNAs (psiRNAs) [ 62 ]. However, integrated pathway analysis showed that miRNAs correlated with protein levels, meaning that, also when mRNA is degraded, proteins are still produced.…”
Section: Discussionmentioning
confidence: 99%
“…The cap mimics in synthetic mRNA were designed and made in order to enhance its translation efficiency and stability, as well as to reduce intracellular innate immunogenicity by impeding stimulation of RIG-I [ 35 , 36 ] ( Fig. 2 B ).…”
Section: Chemical Modifications Of Synthetic Mrnamentioning
confidence: 99%